2022
DOI: 10.1021/acs.biomac.2c00032
|View full text |Cite
|
Sign up to set email alerts
|

Fibrous Structure and Stiffness of Designer Protein Hydrogels Synergize to Regulate Endothelial Differentiation of Bone Marrow Mesenchymal Stem Cells

Abstract: Matrix stiffness and fibrous structure provided by the native extracellular matrix have been increasingly appreciated as important cues in regulating cell behaviors. Recapitulating these physical cues for cell fate regulation remains a challenge due to the inherent difficulties in making mimetic hydrogels with well-defined compositions, tunable stiffness, and structures. Here, we present two series of fibrous and porous hydrogels with tunable stiffness based on genetically engineered resilin-silk-like and resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…4 A and E, compared with the control group and the CEL group, the collagen secretion determined by sirius red staining of BMSCs treated with P@CEL or HP@CEL were significantly increased. These colorimetric analyses demonstrated that coincubation with the hydrogel facilitated the proliferation and differentiation of BMSCs, which may be attributed to the HA components and ECM-like 3-dimensional microstructure of the hydrogel [ 30 , 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…4 A and E, compared with the control group and the CEL group, the collagen secretion determined by sirius red staining of BMSCs treated with P@CEL or HP@CEL were significantly increased. These colorimetric analyses demonstrated that coincubation with the hydrogel facilitated the proliferation and differentiation of BMSCs, which may be attributed to the HA components and ECM-like 3-dimensional microstructure of the hydrogel [ 30 , 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…Lou et al [ 76 ] showed that human pluripotent stem cells changed their spheroid formation behavior when different fiber concentrations of NFC hydrogel were applied. Regarding endothelial differentiation, studies have shown differing differentiation potential of mesenchymal stromal cells depending on the scaffold stiffness [ 77 , 78 , 79 ]. With respect to stiffness control, NFC hydrogel could become a highly beneficial material since it has a fiber concentration directly proportional to the mechanical properties [ 25 ] that can easily be adjusted when needed by diluting the hydrogel or concentrating the dried form of NFC, as explained in our previous studies [ 80 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many in vitro experiments have demonstrated that substrates mimicking tissue-specific moduli can promote the differentiation of stem cells to specific tissue lineages. [16] For example, the soft matrix (<5 Kpa) inhibits cytoskeleton organization and induces differentiation of stem cells to adipocytes and endothelial cells. [17] However, current mechanobiological training studies have only been applied to enhance exogenous cell transplantation, and its potential to improve endogenous regeneration needs to be further explored.…”
Section: Introductionmentioning
confidence: 99%